Analisis Pengaruh Gaya Kepemimpinan, Motivasi Dan Lingkunganan Kerja Terhadap Kinerja Pegawai Kantor Dinas Sosial Pemerintah Kabupaten Muna Barat - Laede, Asmawati; Mallongi, Syahrir; Amir Mahmud (Innovative: Journal Of Social Science Research, 2025)
This study aims to analyze the influence of leadership style, work motivation, and work environment on employee performance at the Social Service Office of the Government of Muna Barat Regency. The research background is based on the low productivity and effectiveness of civil servants (ASN), as seen in delays in program implementation, low employee initiative, and suboptimal quality of public services. These issues are believed to be related to ineffective leadership styles, low work motivation, and an unconducive work environment. This research employs a quantitative approach with an explanatory research design. The population consists of 62 employees, including civil servants, government contract staff (PPPK), and honorary employees, using a saturated sampling technique. Data were collected through questionnaires, observations, and interviews, and analyzed using multiple linear regression analysis to examine the partial and simultaneous effects among variables. The results reveal that (1) leadership style has a positive and significant effect on employee performance, (2) work motivation has a positive and significant effect on employee performance, (3) the work environment also positively and significantly affects employee performance, and (4) the three variables simultaneously have a positive and significant impact on improving employee performance at the Social Service Office of Muna Barat Regency. The findings are expected to provide a foundation for local government in formulating strategies to enhance civil servant performance through participative leadership, increased work motivation, and the creation of a comfortable and productive work environment. Keywords: Leadership Style, Work Motivation, Work Environment, Employee Performance